Prinsip Kedaulatan Permanen atas Sumber Daya Alam dan Implikasinya terhadap Kewenangan Negara dalam Mengatur Investasi Langsung Asing - Muh. Thorieq Erzulsyah Mahmud (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article examines the fundamental clash between the principle of Permanent Sovereignty over Natural Resources (PSNR) and the international legal framework for the protection of Foreign Direct Investment (FDI). This research aims to answer two main questions: first, how PSNR legitimizes the authority of the host state to regulate FDI; and second, what are the implications of exercising such authority on the fulfillment of the Fair and Equitable Treatment (FET) standard and the prohibition of indirect expropriation in investment agreements. Using a normative juridical research method, this article analyzes international legal doctrines, Indonesian laws and regulations, as well as international arbitration awards and WTO panel reports. The analysis reveals that PSNR provides a strong juridical basis for states to implement various forms of control over FDI in the natural resources sector. However, this authority is increasingly constrained by investment treaty obligations, particularly through the broad interpretation of the FET standard and the prohibition of indirect expropriation. This phenomenon has prompted states, including Indonesia, to actively recalibrate their international investment agreements to reclaim policy space and reassert their economic sovereignty.